Indenture, Camden County, 1882 - State of Georgia, Camden County (Valdosta, GA: Valdosta State University Archives and Special Collections, 2020, 1882)
Indenture, Camden County. Handwritten record on typewritten Warrantee Deed form. Indenture between Isabel Adams and Asa Stafford for 300 acres. Published by J.W. Burke & Co., Stationers, Stereotypers, Printers, and Binders, Macon, Ga.. Camden County, Georgia. Dec 8, 1882. 3 pages.
1 electronic document [PDF/A]. Includes TIFF and JP2 images. Digitized by the Digital Library of Georgia, September 2019.
Keywords: Deeds; Camden County (Ga.); Court Records; Records and correspondence; Trust indentures